Alternative bootstrap confidence regions for multiple correspondence analysis - Ringrose, Trevor J. (Taylor & Francis, 2025)
A new approach for constructing elliptical bootstrap confidence regions for Multiple Correspondence Analysis is proposed, where the difference in method follows directly from the adoption of a different objective criterion to previous approaches. This includes a new correction for the well-known problems caused by the diagonal of the Burt matrix. Simulation experiments show that the method performs reasonably well in many cases, with exceptions being noted. Simulated data sets with known structure are also used to illustrate cases where the proposed method produces results in line with what would be expected, but some alternatives do not.
Keywords: Bootstrapping; Burt matrix; Confidence region; Correspondence analysis; Stability